Post-operative complications in elderly patients undergoing hip fracture surgery: An observational study - Sanjeev Kumar Kare; Korada Ravi Kumar; Lukalapu Prasanna Kumar; Nagendra Naidu B (Asian Journal of Medical Sciences, 2024)
Background: Hip fractures in elderly patients are a significant health-care concern due to their high morbidity and mortality rates. Aims and Objectives: This study aims to analyze post-operative complications in this demographic to improve care strategies. Materials and Methods: This observational study included 100 patients aged between 65 and 90 years, undergoing hip fracture surgery. The cohort comprised 40% males and 60% females. Patients underwent either total hip replacement (30%) or internal fixation (70%). We tracked post-operative complications within the first 30 days, mortality and reoperation rates, and recovery and rehabilitation outcomes over 6 months. Results: Post-operative complications were reported in several categories: Infection (10%), cardiovascular (15%), respiratory (12%), renal (5%), neurological (8%), and gastrointestinal (6%). The most common infections were superficial wound infections (6%) and deep infections (4%). Cardiovascular complications included arrhythmias (8%), myocardial infarction (4%), and venous thromboembolism (3%). Pneumonia (7%), acute respiratory distress syndrome (3%), and pulmonary embolism (2%) were the primary respiratory complications. The study also recorded a 4% 30-day mortality rate and a 7% reoperation rate. The average hospital stay was 7 days, with 60% of patients requiring post-discharge rehabilitation. At 6-month post-surgery, 70% of patients had achieved complete recovery. Conclusion: The study highlights a significant incidence of post-operative complications among elderly patients undergoing hip fracture surgery. The findings underscore the need for comprehensive perioperative care and vigilant monitoring to mitigate these risks. The data also stress the importance of post-discharge rehabilitation in enhancing recovery outcomes.